Método de compensación de acoplamiento mutuo y difracción electromagnética en arreglos de antenas de microtira para GNSS - Marranghelli, Ezequiel Alejandro (2016)
An electromagnetic effects compensation method for antenna array radiation patterns is proposed. Mutual coupling (AM) and electromagnetic diffraction (DE) are main responsible of element radiation patterns distortions on antenna arrays. A linear transformation can be made for undesired effects compensation and differences between radiating elements can be suppressed on some desired direccion of arrivals. This allows simple processing techniques to be employed on later stages of an antenna array. An analysis of a suitable four element plane array is presented. The performance of this method is proved by means of a simulated application example of interference cancellation.